Telegram Based Mobile Terminal for Body Temperature Data Storage of COVID-19 Patients - Sucipto, Putra Wisnu Agung; Rahmanto, Raden Hengki (LPPM Universitas Islam 45 Bekasi, 2020)
Health monitoring reports against COVID-19 suspect must be presented every day at 7 o’clock in the morning and 7 o’clock at night. In this report, every patient vital signs must be monitored in order to prevent a potential decline in the level of health from the patient. One of the symptoms observed in this monitoring is a change in body temperature. This monitoring should be carried out without touching the patient’s skin to reduce potential risks of droplets that contain the virus from spreading. This work proposes an idea related to non-contact temperature monitoring which is suitable to use in this pandemic condition. This idea realization process by building a data storage terminal for body temperature scans that is mobile, cheap and has a large storage capacity. This mobile terminal is an integration of the MLX90614 a temperature sensor series, Arduino UNO and Telegram apps. In addition, the communication process between the sensor and the Telegram apps utilizes the GPRS cellular network services. Before arriving at the Telegram apps, this data will pass through gateway site which acts as a collector and relay. In the process of sending the temperature data is then converted into two body temperature categories, normal temperature and abnormal temperature. Based on the trial results that have been carried out, this system consumes 2A of current and 5V of voltage. The communication time duration between the temperature data acquisition system and the collector site is 28 seconds. While the length of time for sending the data from the collector site to the Telegram apps is 8 seconds